(untitled) (Al-Academy, 2017)
Our research which is under the name "Polarization and Communication mechanism in the formation of green industrial products " The problem of the research focuses in identifying what is polarization and its function mechanisms , by displaying the inventive and creative cases of the designer in how to exploit the industrial products and its recycling process to attract the user and recipient by asserting on the values of beauty of the appearance of the industrial product with the attraction Of the user and the recipient with the new function of that product and how its different from the function achieved by the old product , with consideration of nature and its preservation . The results of the research were as following : The designer employed polarization as a mechanism to communicate between the recipient or user and the industrial product , to determine time and place of the presence of the inventor of an item or several items which was used to perform a different shape and function , that is different from the current green design of the industrial product , the polarization of the user and recipient by the awkward ideas and the attractive display to produce useful products for mankind instead of causing damage and pollution of planet earth , where we live.